2002
DOI: 10.2460/javma.2002.220.1341
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ameroid ring constrictors for the management of single extrahepatic portosystemic shunts in cats: 23 cases (1996–2001)

Abstract: Placement of an ARC on single extrahepatic PSS in cats resulted in low surgical complication and perioperative mortality rates, but most cats did have substantial postoperative complications. Persistent shunting was common, although many cats with persistent shunting were clinically normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
208
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(219 citation statements)
references
References 30 publications
8
208
1
2
Order By: Relevance
“…Reported clinical signs were consistent with those previously reported. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] There were 100 extrahepatic shunts and 11 intrahepatic shunts. All 5 cats had extrahepatic shunts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported clinical signs were consistent with those previously reported. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] There were 100 extrahepatic shunts and 11 intrahepatic shunts. All 5 cats had extrahepatic shunts.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] The rationale for slow attenuation is manifold, including reduced risk of life-threatening portal hypertension, speculation that slow occlusion may reduce the risk of post-ligation neurologic dysfunction, reduced operating time, less extensive intraoperative monitoring, and the fact that animals undergoing complete shunt occlusion have a better long-term prognosis than those undergoing partial attenuation only. 13,14 Two methods of slow occlusion using extravascular techniques have been reported: the ameroid constrictor (ameroid ring) [2][3][4][7][8][9]11,12 and cellophane bands. 1,5,10 Results of ameroid constrictor application have been encouraging, although a high incidence of multiple acquired shunts has been identified in published studies and anecdotally ( RM Bright, personal communication, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…19,21 Another study of clinical results after AC in 24 cats with single extrahepatic PSS reported that 8 of 14 cats (57%) had persistent shunting 8-10 weeks after surgery. 22 Use of the AC in combination with a portocaval venograft and complete ligation of single intrahepatic PSS was associated with an even higher rate of continued shunting, with multiple extrahepatic shunts being identified in 4 of 8 dogs at long term follow-up. 8 Portal hypertension likely occurred in these animals because the hepatic microvasculature was unable to compensate for the increased blood flow resulting from premature occlusion of the PSS by the AC.…”
mentioning
confidence: 95%
“…[3][4][5][6][7] An alternative method is to use surgical techniques that achieve gradual progressive closure of the CPS such as perivascular ameroid constrictors, cellophane banding, and intravascular thrombogenic coils. [8][9][10][11][12][13][14][15] The prognosis after surgical intervention remains unpredictable and recurrence or persistence of clinical disease has been documented with all techniques used for shunt attenuation. 2,6,[8][9][10]12,[14][15][16] Poorly developed portal vasculature cranial to the CPS and the degree of shunt closure have been reported to determine clinical outcome after partial shunt ligation.…”
mentioning
confidence: 99%